Kebijakan Digitalisasi dalam Pendidikan Bahasa Mandarin di Tingkat Sekolah Dasar - Patrilia Chandra, Shyta; Erni Murniarti (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the policy basis for digitalization in education and identify innovative and enjoyable digital media implementations in Mandarin Chinese language learning at the elementary school level. The research method used was a qualitative approach with a literature review, which involved identifying, understanding, analyzing, and synthesizing various literature sources relevant to the research topic. The results show that the digitalization policy in Indonesia is supported by strong regulations, such as the implementation of an electronic-based government system, the Merdeka curriculum, and national education standards that encourage the integration of technology in learning. The implementation of digital media such as dictionary applications, game-based learning platforms, and interactive audio-visual media has been proven to increase student interest, motivation, and understanding in learning the complex Mandarin Chinese language. The conclusion of this study is that digitalization in education has a positive contribution to the effectiveness of Mandarin Chinese language learning in elementary schools. Therefore, policy support, infrastructure, and teacher competency development are needed to ensure optimal and sustainable use of digital technology.   Keywords: Digitalization in Education, Mandarin Chinese, Learning Motivation